2020
DOI: 10.3390/ijerph17124533
|View full text |Cite
|
Sign up to set email alerts
|

Stress Measured by Allostatic Load Varies by Reason for Immigration, Age at Immigration, and Number of Children: The Africans in America Study

Abstract: Stress leads to physiologic dysfunction and cardiometabolic disease. Allostatic load score (ALS) measures stress-induced cardiovascular, metabolic, and inflammatory biomarkers. We estimated the odds of high ALS by reason for and age at immigration, duration of American residence, number of children, and socioeconomic status in 193 African immigrants (male: 65%, age 41 ± 10 y (mean ± Standard Deviation (SD)), range 22–65 y). ALS was calculated with High-ALS defined as ALS ≥ 3.0 and Low-ALS defined as ALS < 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Evidence linking cultural continuity in childhood to lower levels of stress, resilient behavior, and less cardiometabolic disease in adulthood was powerfully presented in a study by Currie et al of indigenous adults living in Western Canada [24]. The value of family support on mitigating adverse cardiometabolic health was also evident in our earlier investigations in which we reported that immigrants who came to the United States for family reunification had lower allostatic loads than immigrants who were refugees or seeking asylum [3].…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Evidence linking cultural continuity in childhood to lower levels of stress, resilient behavior, and less cardiometabolic disease in adulthood was powerfully presented in a study by Currie et al of indigenous adults living in Western Canada [24]. The value of family support on mitigating adverse cardiometabolic health was also evident in our earlier investigations in which we reported that immigrants who came to the United States for family reunification had lower allostatic loads than immigrants who were refugees or seeking asylum [3].…”
Section: Discussionmentioning
confidence: 67%
“…2 Chi-square or unpaired t-test. 3 Variables used to calculate CVD-Risk. 4 Married or living with partner (category includes: never married, separated, divorced, widowed).…”
Section: Cultural Identitymentioning
confidence: 99%
See 2 more Smart Citations
“…In this line, the most vulnerable group among immigrants is that of refugees, who, due to the circumstances surrounding the abandonment of the country of origin, are more vulnerable to mental health problems [ 22 ] and have to face many difficulties to integrate into the host country [ 2 , 23 ]. As described by Tribe [ 24 ], the circumstances in which they leave their countries are very different between the two groups:…”
Section: Introductionmentioning
confidence: 99%